Aurora Observing and Recording Nature's Spectacular Light Show - Bone, Neil.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2007)
The uniquely beautiful light display of an aurora is the result of charged particles colliding with tenuous atmospheric oxygen and nitrogen, more than 60 miles above the Earth, when the magnetosphere is disturbed by changes in the solar wind. Often - and incorrectly - regarded as being confined to high northern and southern latitudes, major auroral displays are visible from even the southern USA and the south of England, and occur perhaps twenty times in each eleven-year sunspot cycle. Major auroral storms always cause great interest and excitement in the media, and of course provide practical astronomers with the opportunity to study and image them. This book describes the aurora from the amateur observational viewpoint, discusses professional studies of auroral and geomagnetic phenomena to put amateur work in context, and explains how practical observers can go about observing and recording auroral displays.
Atmospheric Phenomena -- Causes of the Aurora -- Auroral Forecasting -- Observing the Aurora -- Historical Aurorae and More Recent Events -- Aurora Elsewhere -- Early observers and theorists of the aurora classed it along with other atmospheric phenomena as a “meteor.” In common with many of his other ideas that remained unchallenged until well into the sixteenth century, Aristotle’s fourth century BC view of these events being the result of ignition of rising vapors belowthe innermost celestial sphere prevailed for some time. An alternative, proposed by the Roman philosopher Seneca in his Questiones Naturales, was that aurorae were flames viewed through chasmata—cracks in the heavenly firmament. -- Noctilucent Clouds and other Phenomena.
Keywords: Astronomy; Space sciences; Observations, Astronomical; Astronomy—Observations.; Popular Science in Astronomy; Space Sciences (including Extraterrestrial Physics, Space Exploration and Astronautics).; Astronomy, Observations and Techniques